Implementasi Program Pengembangan Anak Usia Dini Holistik Integratif pada RA Se Sumatera Barat: Analisis Kesenjangan Layanan dan Hambatan Lintas Sektor - Afrizal, Afrizal; Ritonga, Mahyudin; Yulitri, Rina (Institut Agama Islam Negeri Kerinci, Indonesia, 2025)
Abstract. This study aims to analyze the implementation of the Holistic Integrative Early Childhood Development (PAUD-HI) program at Raudhatul Athfal (RA) institutions across West Sumatra Province. The PAUD-HI program is a national initiative designed to ensure comprehensive early childhood services through the integration of education, health, nutrition, parenting, and child protection within a unified framework. This research employed a quantitative descriptive approach, with data collected using an instrument developed based on the components outlined in the Guidelines for Holistic Integrative Early Childhood Development. The instrument was also validated by three experts in the field of early childhood education and holistic integrative programs to ensure content validity. The findings indicate that the highest level of implementation occurred in the education component (85%), followed by health, nutrition, and care (72%); family and community participation (70%); child protection and welfare (68%); and parenting and mental health (58%). The main barriers identified include limited training and socialization, incomplete understanding of the PAUD-HI concept, lack of supporting human resources such as health workers and child psychologists, low teacher competence in health and child protection, limited operational funding, and ineffective cross-sector coordination. The study concludes that the implementation of PAUD-HI in RA institutions across West Sumatra has shown progress, yet remains constrained by systemic factors such as human resource capacity, funding, and inter-agency coordination. Strengthening teacher training, operationalizing cross-sector partnerships, and providing sustainable financial support are recommended to ensure the effectiveness of holistic services in early childhood education.